MODEL OF LATERITE NICKEL DEPOSITS BASED ON LGSO AND HGSO VALUES PT MITRA KARYA AGUNG LESTARI - Asmiani, Nur; Thamsi, Alam Budiman; Nompo, Supardin; Bakri, Suryanto; Tukloy, Muh. Yusril Affandy; Harmitun, Harmitun (Engineering Faculty Universitas Lampung, 2024)
The laterite nickel deposit model provides information about the form of laterite nickel deposits below the surface, which can be used as one of the considerations in the implementation of mining activities. The purpose of conducting this research is to determine the distribution model of nickel laterite deposits in 3 dimensions (3D) and to determine the amount of nickel laterite reserves based on high-grade saprolite ore (HGSO) and low-grade saprolite ore (LGSO) values in the DH Block. In this research, Inverse Distance Weighted (IDW) is used to estimate nickel laterite resources, which are applied using mining software Surpac 6.3.2 to produce a model in 3D form. The data used are laterite nickel content data (assay), x, y, and z coordinate data (collar), survey data, and lithology data. Based on IDW estimation results with a Cut Off Grade (COG) value of 1.3 in the DH Block of PT Mitra Karya Agung Lestari, High-Grade Saprolite Ore (HGSO) values were obtained at Ni content 1.7 and Low-Grade Saprolite Ore (LGSO) at Ni content 1.3, with a tonnage value of 111.994 tons of HGSO and 371.044 tons of LGSO.